Wildlife of Nebraska a natural history - Johnsgard, Paul A. (University of Nebraska Press, 2020)
"Wildlife of Nebraska surveys the variety and biology of Nebraska's terrestrial vertebrates by describing the ecology and biology of the state's birds, its mammals, and its reptiles and amphibians"--